Impaired NFKBIE gene function decreases cellular uptake of methotrexate by down-regulating SLC19A1 expression in a human rheumatoid arthritis cell line. Issue 4 (3rd July 2016) - Imamura, Hitoshi; Yoshina, Sawako; Ikari, Katsunori; Miyazawa, Keiji; Momohara, Shigeki; Mitani, Shohei
Abstract: Objective : A non-synonymous single nucleotide polymorphism (nsSNP, rs2233434, Val194Ala) in the NFKBIE (nuclear factor of kappa light polypeptide gene enhancer in B-cells inhibitor, epsilon) gene is known to be a rheumatoid arthritis (RA) susceptibility polymorphism in the Japanese RA population and could be closely associated with nuclear factor kappaB (NF-κB) activity. Inflammation caused by RA is sometimes associated with changes in expression levels of MTX (methotrexate) pathway-related genes. It is of interest to examine whether the NFKBIE gene had any influences on the mode of MTX action. Methods : Both knockdown of NFKBIE gene expression and overexpression of wild-type NFKBIE and Val194Ala mutation were performed. A transfected human RA synovial cell line was cultured and then gene expressions in the MTX pathway were measured. In addition, we measured the uptake and efflux of MTX derivatives under the NFKBIE knockdown condition. Results : Knockdown of NFKBIE reduced the mRNA for SLC19A1, a main MTX membrane transporter, and the intracellular accumulations of MTX derivatives. Moreover, our experiments also confirmed that overexpression of Val194Ala mutant NFKBIE decreased the SLC19A1 mRNA when compared to that of wild-type NFKBIE . Conclusions : We suggest that the impairment of NFKBIE gene function can reduce the uptake of MTX into cells, suggesting that the gene is an important factor for the RA outcome.